The Influence of Visual Content on TikTok Social Media Toward Customer Engagement in the Food and Beverage Industry on Product Purchase Decisions - Dwi Erlanda Anggara; Tri Inda Fadhila Rahma; Nursantri Yanti (Celebes Scholar pg, 2025)
The purpose of this research is to provide insights into the extent to which visual content on TikTok influences customer engagement, how significantly customer engagement affects purchasing decisions, and the relationship between visual content on TikTok and customer engagement in making product purchase decisions. This study employs a quantitative method with an explanatory research approach. Data were collected through questionnaires distributed to 80 consumers of Sinar Utama chicken noodles. The analysis technique used is Path Analysis via SmartPLS software version 3.3. The measurements applied include the outer model assessment, mediation test, and inner model assessment. The findings from the field demonstrate that: (1) Attractive visual content significantly enhances customer engagement because strong visuals are able to capture attention, thereby encouraging interactions that increase interest in the product. (2) Customer engagement plays a crucial role in influencing purchasing decisions by building trust, loyalty, and emotional connections, which can drive customers to buy. (3) Customer engagement serves as a mediator between attractive visual content and purchasing decisions, as emotional involvement and customer interaction with visual content strengthen the decision-making process to purchase the product.